Timber Reuse in Mediaeval Churches of Finland - Dalheimer, Franziska; Savolainen, Panu; Laine, Laura; Välimäki, Reima; Aakala, Tuomas (Walter de Gruyter GmbH, 2026)
Reusing construction materials is as old as construction itself. The most prevalent historical examples of reuse, especially spolia, consist of buildings made of hard and durable materials, such as stone and bricks. We examined circular wood use, including reuse, remanufacturing and recycling, on large-scale mediaeval construction sites, specifically in Finland’s mediaeval stone churches. In the Nordic countries, especially Denmark and Sweden, the reused pieces from older churches were intentionally positioned in niches, doorways, and window sills.
In this study, we reflect on two standing examples of the mediaeval reuse of sacral timber from Finland: St. Mary’s Church in Pohja and St. Henry’s Church in Pyhtää. Our study aimed to highlight the practical starting points and motivations for reclaiming timber and the possible intentional positioning of sacred wood in ecclesiastical buildings. The analysed Finnish cases could currently be considered examples of a local ‘circular material economy’, with opportunities for recycling and reuse. Our research shows that ritualistic or artistic expressions did not motivate the Finnish reuse cases. Instead, the reuse helped reduce the time- and labour-intensive work of the local mediaeval community, given the modest available energy surplus for large-scale construction projects.